A transgenic zebrafish liver tumor model with inducible Myc expression reveals conserved Myc signatures with mammalian liver tumors - Zhen Li; Weiling Zheng; Zhengyuan Wang; Zhiqiang Zeng; Huiqing Zhan; Caixia Li; Li Zhou; Chuan Yan; Jan M. Spitsbergen; Zhiyuan Gong (The Company of Biologists, 2013)
SUMMARY Myc is a pleiotropic transcription factor that is involved in many cellular activities relevant to carcinogenesis, including hepatocarcinogenesis. The zebrafish has been increasingly used to model human diseases and it is particularly valuable in helping to identify common and conserved molecular mechanisms in vertebrates. Here we generated a liver tumor model in transgenic zebrafish by liver-specific expression of mouse Myc using a Tet-On system. Dosage-dependent induction of Myc expression specifically in the liver was observed in our Myc transgenic zebrafish, TO(Myc), and the elevated Myc expression caused liver hyperplasia, which progressed to hepatocellular adenoma and carcinoma with prolonged induction. Next generation sequencing-based transcriptomic analyses indicated that ribosome proteins were overwhelmingly upregulated in the Myc-induced liver tumors. Cross-species analyses showed that the zebrafish Myc model correlated well with Myc transgenic mouse models for liver cancers. The Myc-induced zebrafish liver tumors also possessed molecular signatures highly similar to human those of hepatocellular carcinoma. Finally, we found that a small Myc target gene set of 16 genes could be used to identify liver tumors due to Myc upregulation. Thus, our zebrafish model demonstrated the conserved role of Myc in promoting hepatocarcinogenesis in all vertebrate species.